The perioperative and anesthetic adverse events in Thailand (PAAD Thai) study: Peripheral neurological deficit in 2,000 incident reports - P. Vorapaluk (2019)
© Journal of the medical association of Thailand. Background: Perioperative peripheral neurological deficit is an uncommon but debilitating complication after surgery. Despite the awareness of the injury after surgery, there are still some neurological deficit events that occurs. Objective: To investigate the contributing factors and preventive strategies of peripheral neurological deficit incidents. Materials and Methods: The authors conducted the prospective, multi-centered, observational study as part of the Perioperative and Anesthetic Adverse Events Study in Thailand (PAAd Thai) among 22 hospitals from all regions across Thailand. The critical incident reports during a 12-month-period, between January 1 and December 31, 2015, were reviewed and analyzed by three senior anesthesiologists to identify possible contributing factors and potential corrective strategies. The data were reported using descriptive statistics. Results: Among the first 2,000 critical incidents that occurred in 2015, there were 19 perioperative peripheral nerve neurological deficits reported under both general and regional anesthesia. The most common reported events were lumbosacral injury (42.1%) and brachial plexus (31.6%). Reported incidents were related to surgery (26.3%), anesthesia (36.8%), and malpositioning (36.9%). The major contributing factor was inexperience, while suggested corrective strategies included having vigilance and experience by providing quality assurance activity and additional training. Conclusion: Perioperative peripheral neurological deficit after anesthesia might be related to surgery, anesthesia (both general anesthesia and regional anesthesia), or position during operation. Having more vigilance and experience, including training, for anesthesia providers may prevent this catastrophic complication.